Palmitoylation regulates the magnitude of HCN4-mediated currents in mammalian cells - Congreve, Samitha Dilini; Main, Alice; Butler, Andrew S.; Gao, Xing; Brown, Elaine; Du, Chunyun; Choisy, Stephanié C.; Cheng, Hongwei; Hancox, Jules C.; Fuller, William (Frontiers in Physiology, 2023)
The sinoatrial node (SAN) and subsidiary pacemakers in the cardiac conduction system generate spontaneous electrical activity which is indispensable for electrical and therefore contractile function of the heart. The hyperpolarisation-activated cyclic nucleotide-gated channel HCN4 is responsible for genesis of the pacemaker “funny” current during diastolic depolarisation. S-palmitoylation, the reversible conjugation of the fatty acid palmitate to protein cysteine sulfhydryls, regulates the activity of key cardiac Na+ and Ca2+ handling proteins, influencing their membrane microdomain localisation and function. We investigated HCN4 palmitoylation and its functional consequences in engineered human embryonic kidney 293T cells as well as endogenous HCN4 in neonatal rat ventricular myocytes. HCN4 was palmitoylated in all experimental systems investigated. We mapped the HCN4 palmitoylation sites to a pair of cysteines in the HCN4 intracellular amino terminus. A double cysteine-to-alanine mutation CC93A/179AA of full length HCN4 caused a ∼67% reduction in palmitoylation in comparison to wild type HCN4. We used whole-cell patch clamp to evaluate HCN4 current (IHCN4) in stably transfected 293T cells. Removal of the two N-terminal palmitoylation sites did not significantly alter half maximal activation voltage of IHCN4 or the activation slope factor. IHCN4 was significantly larger in cells expressing wild type compared to non-palmitoylated HCN4 across a range of voltages. Phylogenetic analysis revealed that although cysteine 93 is widely conserved across all classes of HCN4 vertebrate orthologs, conservation of cysteine 179 is restricted to placental mammals. Collectively, we provide evidence for functional regulation of HCN4 via palmitoylation of its amino terminus in vertebrates. We suggest that by recruiting the amino terminus to the bilayer, palmitoylation enhances the magnitude of HCN4-mediated currents, but does not significantly affect the kinetics.